2005
DOI: 10.1038/sj.bjc.6602312
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of information about HPV in cervical screening: a qualitative study

Abstract: Introducing human papillomavirus (HPV) testing into cervical cancer screening has the potential to change the way that women understand cervical cancer, the psychological impact of abnormal screening results and the likelihood of future participation in screening. The study used in-depth interviews to examine how women make sense of information about HPV in the context of cervical cancer screening. A total of 74 women were recruited following participation in HPV testing. Women varied widely in their beliefs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
2
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 20 publications
7
75
2
2
Order By: Relevance
“…Anxiety was often compounded by lack of knowledge about HPV. These responses are consistent with results from an earlier study [7,15].…”
Section: Initial Anxiety That Was Then Resolvedsupporting
confidence: 92%
“…Anxiety was often compounded by lack of knowledge about HPV. These responses are consistent with results from an earlier study [7,15].…”
Section: Initial Anxiety That Was Then Resolvedsupporting
confidence: 92%
“…In preliminary studies of both adults and adolescents, HPV testing has been associated with anxiety, distress, perceived stigma, and fear of further testing and treatment procedures. (13,15,16,25) These types of responses may adversely impact adolescent decisions about future STI screening and follow-up. (26,27) Our previous work has demonstrated that cognitive understanding of HPV infection and Pap tests is a key factor in predicting psychosocial and behavioral responses to HPV infection and abnormal Pap tests.…”
Section: Discussionmentioning
confidence: 99%
“…(3)(4)(5)(6)(7)(8) Despite its high prevalence and potentially serious consequences, adolescent and young adult women demonstrate poor understanding of HPV and Pap tests. (9)(10)(11)(12)(13)(14) This lack of knowledge may lead to significant psychosocial distress in women diagnosed with HPV or abnormal Pap tests, including fear and anxiety. Research suggests that these types of negative responses could decrease follow-up for diagnostic or treatment procedures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HPV is known to be highly infectious, but in the majority of cases, the immune system is able to clear the infection or suppress the onset of symptoms. However, the virus may remain dormant in the body for many years (Waller, McCaffery, Nazroo, & Wardle, 2005). In such cases, it is important to help control the spread of the virus.…”
Section: Tablementioning
confidence: 99%